SURVIVE AFTER THE COVID-19 PANDEMIC ON UMRAH AND HAJJ TRAVEL INDUSTRY, WHAT IS THE BEST MARKETING STRATEGY? - Nofrizal, Nofrizal; Aznuriyandi, Aznuriyandi (Jurnal Ilmiah Ekonomi Dan Bisnis, 2024)
The COVID-19 pandemic and Russian and Ukrainian wars condition have made the entire industry unstable condition, several Umrah travel industries are adjusting to the consequences of this outbreak with business closures, layoffs, and sales of business units. But at this time after the pandemic began to improve with the permitting of the implementation of Hajj and Umrah in 2022 by the Kingdom of Saudi Arabia, the Umrah travel industry must develop a health strategy to survive after the pandemic. The purpose of this article is to find alternative marketing strategies using SWOT and AHP analysis. This type of research is descriptive using a survey approach, Interviews, FGD, Direct experiments, Observations, and literature studies. The object of this research is 30 units of Umrah travel, The results of the study recommend three alternative strategies, namely improving service quality, digital marketing, and reducing prices. Practical implications and socially from this research the travel industry can take advantage of this strategy to implement marketing strategies and add to the literature of marketing strategies and increase consumer interest in traveling.